Analysis of the Concept of Al-Hubb in the Thought of Zainal Arifin Abbas (1911-1977) - Habibi, M. Yusuf; Andy, Safria; Rambe, Uqbatul Khoir (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2023)
This article seeks to explore Zainal Arifin Abbas' conceptualization of al-Hubb (Love). It poses two central questions: firstly, what is Zainal Arifin Abbas' interpretation of the concept of al-Hubb, and secondly, how does he construct the foundational framework for interpreting al-Hubb? This qualitative research relies on both primary and secondary data sources. The primary data comprises Zainal Arifin Abbas' writings in Tafsir Al-Qur'an al-Karim and Ilmu Tasawuf. Concurrently, secondary data, including articles, dissertations, and supporting information, is incorporated. The data is subjected to content analysis. The findings reveal that al-Hubb serves as a fundamental determinant of behavior, guiding individuals towards peace, security, and a devout faith in brotherhood. Zainal Arifin Abbas imparts a message of love in his works, emphasizing that love originates from knowledge, familiarity, and the reception of goodness. Artikel ini bertujuan untuk melacak konsepsi pemikiran Zainal Arifin Abbas mengenai Al-Hubb (Cinta). Dalam artikel ini mengajukan pertanyaan, pertama bagaimana konsep penafsiran al-Hubb menurut Zainal Arifin Abbas?, kedua, bagaimana konstruksi dasar penafsiran al-Hub menurut Zainal Arifin Abbas?. Penelitian ini berjenis penelitian kualitatif dengan menggunakan dua sumber data yaitu primer dan sekunder. Data primer yang digunakan dalam artikel ini adalah tulisan Zainal Arifin Abbas dalam Tafsir Al-Qur’an al-Karim dan Ilmu Tasawuf. Sedangkan untuk data sekunder yang digunakan adalah artikel, disertasi, atau data-data yang mendukung dalam penelitian ini. Dari data yang ada akan dianalisis dengan menggunakan content analysis. Dari penelitian ini menunjukkan beberapa al-Hubb (Cinta) sebagai landasan bersikap, yang bisa membawakan manusia kepada kedamaian, keamanan, serta keimanan dan persaudaraan yang suci. Zainal Arifin Abbas juga menawarkan pesan cinta (al-Hubb ) dalam beberapa karyanya. Pesan cinta itu memuat asal lahirnya cinta dari pengetahuan dan perkenalan. Dan cinta itu lahir dari kebaikan yang diterima.